Evaluation of the Parenting Program in Kindergarten - Asmawulan, Tri; Hastuti, Isnaini Budi; Fitriyah, Qonitah Faizatul (THUFULA, 2022)
This research is motivated by the low level of understanding of parents about early childhood education. In addition, there is still a lack of synergy between the school and parents in educating children. The method used in this research is qualitative research, with interview, observation and documentation techniques. The results of this study are: a. the parenting program implemented at Al Fajar Kindergarten has generally been running according to the standard parenting activity program, namely the existence of programs related to parent meetings (KPO), parental involvement in class (KOK), parent involvement in joint events (KODAB) , parent consultation days (HKO), and home visits. c. Parenting programs that have been running at Al Fajar Kindergarten include parent meetings, involving parents or guardians in learning activities and institutional activities, consulting children's problems with school consultants, and regular home visits to children. d. The results of the parenting program implementation at Al Fajar Kindergarten show that the better the understanding of parents towards early childhood education, children's health and hygiene, and also the increasing positive synergy between the school and parents.